The formal demonstration of the legimaticy of the categories in the Trascendental Deduction (Edition B) - Másmela Arroyave, Carlos (Estudios de Filosofía, 1990)
The most important and most widely discussed intetpretation of Kant in recent years has been "Die Beweisstruktur von Kants transzendentaler Deduktion", by Dieter Henrich, appearing in PRAUSS, Gerold. Hrsg.; Kant. Zur Deutung seiner Theorie von Erkennen und Handeln. Köln, 1973, p. 90-104. Considered from a juridical point of view, deduction gives a proof of the origin of pure knowledge and shows the scope and limits of its pretensions to legitimacy. Transcendental deduction sets as its goal demonstrating that there is an irrestricted use of the categories in determining a given multiplicity. Henrich concentrates on the proof of the validity of the pure concepts of understanding and its consequent application. The innovation, according to Henrich, consists in talking, not about two proofs -as it has been traditional- but only about one proof having two steps, placed in different passages of the second redaction (B). The first one exposes the restriction of validity (15 - 21) whereas the second one refers to the overcoming of this restriction (26). The first passage shows that all intuitions having unity are under tbe domain of the categories (20). But something essential in the first part of deduction B is still missing for its complete fulfillment. The restriction is overcome in 26, with the thesis of the unity of the formal intuitions of space and time. The present article attempts a detailed analysis of the two steps in the proof proposed in Henrich’s reconstruction, in order to question the suppositions under which the proof of legitimacy can go into effect, together with the ulterior application of the pure concepts of understanding